New species of Anabarhynchus Macquart (Diptera: Therevidae) from arid and monsoon tropical Australia - Ferguson, David J.; Irwin, Michael E. (Zootaxa, 2013)
Anabarhynchus Macquart (1848) is a species-rich gen of therevine Therevidae, with over 90 species described from Aus-tralia alone. Over the past two decades, extensive and intensive malaise trap surveys have revealed that the continent con-tains many additional species to the previous 94 species known; making that genus one of the most species-rich therevid genera in the world. Specimens of these new species are deposited in Australian collections, notably the Australian Mu-seum (AM), Australian National Insect Collection (ANIC), and the Queensland Museum (QM). Here we describe, diag-nose and illustrate ten new species in the genus Anabarhynchus as follows: Anabarhynchus doncollessi sp. n., Anabarhynchus ewamin sp. n., Anabarhynchus lyneborgi sp. n., Anabarhynchus parilus sp. n., Anabarhynchus parkeri sp. n., Anabarhynchus pilbara sp. n., Anabarhynchus ravenshoensis sp. n., Anabarhynchus shiptonsflatensis sp. n., Ana-barhynchus tribulationensis sp. n., Anabarhynchus weipaensis sp. n. These new species add to the faunas known from arid and monsoon tropical Australia.